2007
DOI: 10.1007/s00428-007-0476-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between dendritic cells and nerve fibres in lymphoid organs after oral scrapie exposure

Abstract: In transmissible spongiform encephalopathies (TSEs), the infectious agent, called PrPsc, an abnormal isoform of the cellular prion protein, accumulates and replicates in lymphoid organs before affecting the nervous system. To clarify the cellular requirements for the neuroinvasion of the scrapie agent from the lymphoid organs to the central nervous system, we have studied, by confocal microscopy, the innervations within Peyer's patches, mesenteric lymph nodes and the spleen of mice in physiological conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…10). The absence of a negative eVect of prions upon the neurites network is in accordance with in situ observations made on diVerent species (Dorban et al 2007a;Marruchella et al 2009). …”
Section: Inxuence Of Prp Sc Upon Neurites Outgrowthsupporting
confidence: 90%
See 2 more Smart Citations
“…10). The absence of a negative eVect of prions upon the neurites network is in accordance with in situ observations made on diVerent species (Dorban et al 2007a;Marruchella et al 2009). …”
Section: Inxuence Of Prp Sc Upon Neurites Outgrowthsupporting
confidence: 90%
“…An up-todate in vitro study has shown that infected dendritic cells are able to transmit prions to primary neurons from the CNS by the intermediary of tunneling nanotubes (TNT) (Gousset et al 2009). Previously we have also demonstrated that CD11c-DCs established a lot of contacts with the nerve Wbers inside the mouse Peyer's patches in physiological conditions and following a scrapie challenge (Defaweux et al 2005;Dorban et al 2007a). Similar results have been obtained within sheep Peyer's patches (Marruchella et al 2007;Chiocchetti et al 2008).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The presence of noradrenergic fibers was reported in PPs implying that the sympathetic nerve could play a role in the regulation of the immune response. Noradrenergic axonal fibers are found in close proximity to DCs, 11 plasma cells and in T cell zones 12 . NA can affect DCs migration as well as their cytokine production (i.e., IL12, IL-6 13 ) through the binding to adrenoceptors (β2 13 , α1, 14 α2 15 , 16 ).…”
Section: Intestinal Neuro-immune Interactionsmentioning
confidence: 99%
“…51 These contacts in the peripheral lymph nodes and spleen are assumed to be important for neuroinvasion of the infectious agent. 52,53 Therefore, these findings suggest the possibility that PrP-positive macrophages in Peyer's patches and the spleen may be involved in neuroinvasion, and neuroinvasion can occur a few hours after an oral infection.…”
Section: Discussionmentioning
confidence: 86%